Positioning Aeromonas Infection in Inflammatory Bowel Disease: A Retrospective Analysis - Guedes,Tiago Pereira (2023)
Abstract Background and Aim: Aeromonas are Gram-negative rods known to cause a spectrum of diseases. Inflammatory bowel disease (IBD) is an idiopathic complex condition resulting from interaction of multiple factors. Aeromonas infection in association with IBD is still largely unknown. We aim to look for the significance of Aeromonas infection and for significant differences between IBD and non-IBD patients. Methods: A retrospective observational analysis was performed of all patients positive for Aeromonas in stool cultures, during a 10-year period, from a tertiary and university hospital. Results: Fifty patients were included, 56% male with a mean age of 42.1 years. Thirty-eight (76%) were non-IBD and 12 (24%) IBD patients. IBD patients were more frequently under immunosuppressors. Two patients were asymptomatic and 44% developed mild, 44% moderate, and 16.7% severe infection. The main strains isolated were Aeromonas hydrophila/caviae. Bacterial co-isolation was found in 4 non-IBD and histological findings of cytomegalovirus in 2 IBD patients. Non-IBD patients presented more frequently with fever and IBD patients with bloody diarrhea and abdominal pain. There was higher tendency for severe infection rate in IBD patients with higher antimicrobial therapy use. Steroids were exclusively used in the IBD group. From IBD, 4 patients had the diagnosis of ulcerative colitis and 9 of Crohn’s disease with colonic involvement. Of these patients, 5 received IBD diagnosis after the acute episode of Aeromonas infection. Conclusions: Clinical presentation of Aeromonas infection differs between IBD and non-IBD patients. Non-IBD patients had milder severity of infection with less use of antibiotics. Aeromonas infection seems to greatly contribute to IBD manifestation.